Experimental and applied immunotherapy - Medin, Jeffrey; Fowler, Daniel H. (Humana Press, 2011)
Immunotherapy is now recognized as an essential component of treatment for a wide variety of cancers. It is an interdisciplinary field that is critically dependent upon an improved understanding of a vast network of cross-regulatory cellular populations and a diversity of molecular effectors; it is a leading example of translational medicine with a favorable concept-to-clinical-trial timeframe of just a few years. There are many established immunotherapies already in existence, but there are exciting new cancer immunotherapies just on the horizon, which are likely to be more potent, less toxic.